Gambaran Frekuensi Penggunaan Antimikroba Oral pada Tatalaksana Terapi Pasien Acne Vulgaris di RSUD Toto Kabila Gorontalo - Teti Sutriyati Tuloli; Andi Nabirah Asriastuti; Derina Dwifrila Ridhani Gubali; Jihan Indriatawati; Nensy Toban Rombe; Putri Kartika Adhilia Kahar; Sri Noviani Tolulu (Poltekkes Kemenkes Padang, 2024)
Acne vulgaris is a chronic inflammatory disorder that occurs in the polysebaceous unit and is generally caused by infection with the bacterium Propionibacterium acnes. The role of these bacteria in the pathogenesis of acne is the basis for giving antimicrobials or antibiotics in the management of acne vulgaris therapy, both in topical and oral forms. This study aims to describe the frequency of use of oral antimicrobials in the treatment of acne vulgaris and to determine the accuracy of antibiotic selection based on the severity of acne at Toto Kabila General Hospital, Gorontalo. This type of research is an observational study with a descriptive design and data collection was carried out retrospectively using medical record sheets from patients diagnosed with acne vulgaris. The results showed that of the 6 cases, there were 3 types of oral antibiotics used in the management of acne vulgaris, namely clindamycin, doxycycline and amoxicillin. Oral antibiotic therapy was found to be used alone in 5 cases, consisting of clindamycin 33.3%, doxycycline 33.3%, and amoxicillin 16.7%. While the use of a combination of antibiotics was only found in 1 case, namely a combination of clindamycin and gentamicin cream of 16.7%. Based on these results, it concluded that antibiotic therapy given as monotherapy or a combination of antibiotics in this study is not appropriate because it has the potential for resistance and recommended that all health workers and families pay attention to the use of antibiotics.